Performance analysis of modified secure link state routing protocol. (1st January 2012) - El-said, Shaimaa A.
Secure link state protocol (SLIP) is the most effective scheme proposed so far to protect the internet infrastructure against routing table 'poisoning' attacks. The major disadvantage of the SLIP is its failure in protecting the network in the case of inactive routing table attacks and in some cases of proactive attacks. A successful attempt is carried out to improve the performance of secure link state protocol SLIP applied to protect internet infrastructure in a communication network. A modified secure link state protocol (MSLIP) is proposed to overcome the problems found in the SLIP, since it takes the advantages of SLIP and adds the necessary operations to protect the internet infrastructure in all the cases of inactive and proactive routing attacks. A complete comparison under different scenarios is performed between the performances of MSLIP, SLIP and traditional LS are presented in this work. A sensible results and valuable practical relation are obtained. The results show that the performance of the MSLIP is better than the existing SLIP as well as traditional link secure protocol LS.